ANALISIS ASSESMENT SALES RATIO PADA NILAI JUAL OBJEK PAJAK DENGAN ZONA NILAI TANAH TERHADAP STANDAR YANG DITETAPKAN IAAO - Nurul Azizah Baisaku; Bambang Hendriya Guswanto; Dian Linawati (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
Land values in NJOP used as a basis for taxing land are often different from land values in the Land Value Zone (ZNT). The difference in land values contained in the NJOP and ZNT causes uncertainty about local tax revenue and creates injustice for the government and the community. Based on this, an analysis of Assesment Sales Ratio (ASR) is used to determine the determination of land values in NJOP with ZNT against the standard size determined by the International Association of Assessing Officers (IAAO). The results of the ASR analysis show that the determination of NJOP in Pamijahan Village, Plumbon District, Cirebon Regency is outside the standard range set by the IAAO, which is 0.90 to 1.10 (90% -110%). This can be seen from the results of the measurement of central tendency, which is a mean of 10.53%, a median of 0.1037, and a weighted mean of 6.136%. The comparisons between components of the measurement results of the central tendency indicate the occurrence of regressivity or downtrend. The Assessment Ratio in Pamijahan Village, Plumbon District, Cirebon Regency also did not show good uniformity, as indicated by a COD value of 0.66% and a COV value of 70.02% which were outside the standard set by IAAO i.e. the minimum and maximum values for COD and COV are 5% and 20%, respectively.